Improving Student Learning Achievement in Aqidah Akhlak Learning with The Card Sort Method at MTs Muhammadiyah Panyakalan - Mawati, Yelmi; Faqori, Yudha Bima; Sulaeman, Wono; Suryani, Yani; Risman, Mulia (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the learning achievement of Aqidah Akhlak of class VII students of MTsM Panyalan on the material